2017
DOI: 10.1159/000470853
|View full text |Cite
|
Sign up to set email alerts
|

Selected Food Consumption Mediates the Association between Education Level and Metabolic Syndrome in Korean Adults

Abstract: Background/Aims: Low socioeconomic status (SES) is linked to higher incidence/mortality of cardiovascular disease, but emerging evidence inconsistently reported that education level, a proxy for SES, is related to cardiovascular risk and metabolic syndrome (MetS) in Koreans. Furthermore, limited information is available on whether dietary components would mediate the relationship between education level and cardiovascular risk. We hypothesized that selected food consumption mediates the association between edu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 44 publications
(62 reference statements)
3
34
0
Order By: Relevance
“…Full-text of 308 articles was reviewed and the following 299 articles were excluded (online Supplementary Table S2): 119 studies not related to dietary factors, seventy-seven studies not related to outcome, twenty-four reviews or letters, thirty-eight studies for which no full text was available, twenty-two studies that did not report OR/RR or 95 % CI, eight studies not published in English, six studies that did not report data for fruit or vegetable consumption, two clinical studies, one duplicate study and two studies that focused on patients with specific diseases. As a result, a total of nine articles (5)(6)(7)(8)(9)(10)15,17,20) were identified as eligible for the present meta-analysis ( Fig. 1).…”
Section: Literature Search For Dose-response Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Full-text of 308 articles was reviewed and the following 299 articles were excluded (online Supplementary Table S2): 119 studies not related to dietary factors, seventy-seven studies not related to outcome, twenty-four reviews or letters, thirty-eight studies for which no full text was available, twenty-two studies that did not report OR/RR or 95 % CI, eight studies not published in English, six studies that did not report data for fruit or vegetable consumption, two clinical studies, one duplicate study and two studies that focused on patients with specific diseases. As a result, a total of nine articles (5)(6)(7)(8)(9)(10)15,17,20) were identified as eligible for the present meta-analysis ( Fig. 1).…”
Section: Literature Search For Dose-response Meta-analysismentioning
confidence: 99%
“…However, the results remain controversial. Some studies (5,6) have reported that fruit consumption is significantly associated with a decreased risk of the MetS, while others (7)(8)(9) have shown no association between fruit intake and risk of the MetS. Several studies (9) revealed an inverse association between vegetable intake and risk of the MetS, while others (7,10) showed no relationship.…”
mentioning
confidence: 99%
“…These studies were published between 2007 and 2017, and include twenty cross-sectional, one case-control and five cohort studies. Four of the included studies were performed in European countries (Finland (25,37) , Poland (26) and Portugal (21) ), fourteen studies were conducted in Asian countries (Korea (16,17,20,24,27,30,38) , India (22) , Taiwan (32,40) , Iran (34,39) , Japan (33) and China (29) ), four studies were conducted in the USA (7,19,28,31) and the other four studies were from Chile (35) , Suriname (18) and Brazil (23,36) . Twentythree articles included both male and female participants (7,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(28)(29)(30)(31)(32)(33)(35)(36)(37)(38)…”
Section: Statistical Analysesmentioning
confidence: 99%
“…The sample size ranged from 305 to 27 656 for a total number of 115 727. The criteria for MetS were those of the National Cholesterol Education Program Adult Treatment Panel III in eighteen articles (16)(17)(18)(21)(22)(23)(24)(25)27,28,30,32,(34)(35)(36)(38)(39)(40) , the International Diabetes Federation in three (19,20,33) and the American Heart Association in two studies (7,26) . Moreover, the criteria proposed by Alberti et al were used in two studies (29,37) .…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Thirty-four studies (71.0%) employed a compositional approach to measuring SEP. Of those 34 studies, 17 depended on a single parameter and classified SES level according to a continuous or dichotomous distribution or standardized categori-zation. In these studies, the principal indicators were traditional measures of education [12][13][14][15][16][17][18], household income [19][20][21], and occupation [22,23]. Some studies specified the SES level according to proxy measures such as type of health insurance or health-insurance premium levels, which are determined in proportion to one's comprehensive living status [24][25][26][27][28].…”
Section: Compositional Socioeconomic Position Measuresmentioning
confidence: 99%